Synchronization of Dairy Cows Does Not Limit the Behavioral Response to Treatment in Mixed Treatment Experimental Designs - King, Meagan T. M.; Crossley, Robin E.; DeVries, Trevor J. (Frontiers in Veterinary Science, 2016)
In many research studies, animals assigned to different treatments are housed adjacently or together in a group. One critique of these designs has been the potential role of behavioral facilitation and synchronization between animals on different treatments in mixed treatment groups (heterogeneous groups). To evaluate this, we compared the synchrony of feeding behavior between dairy cows housed in heterogeneous groups to cows exposed to the same treatment simultaneously (homogenous groups). Twenty-four cows were exposed to each of 2 treatments over 21 d in a replicated cross-over design. Treatments were two different schedules of timing of feed delivery: (A) feeding at milking time and (B) feeding halfway between milking times. For the last 7 d of each treatment period, feeding behavior was recorded electronically. Kappa coefficients were calculated for each animal within each group, as an estimate of agreement that any 2 cows within a group (i.e. each individual and each other cow in her group) would both be engaged in feeding activity for any hour of the day. The level of synchrony was similar for cows within homogenous groups (Kappa = 0.31 ± 0.030) compared to cows on the same treatment within heterogeneous groups (Kappa = 0.32 ± 0.037). Within heterogeneous groups, cows on the same treatment were nearly 50% more synchronized with each other than with those on the other treatment (Kappa = 0.22 ± 0.029). These results suggest that synchronization of feeding behavior does not restrict our ability to impose different treatments on individual cows within a group.